Hubungan Self Awareness dengan Hasil Belajar pada Mahasiswa Penerima Kartu Indonesia Pintar - Putri, Ukti Julmi; Yendi, Frischa Meivilona; Syukur, Yarmis; Putra, Febri Wandha; Zola, Nilma (YASIN, 2024)
The Indonesian Smart Card (KIP) recipient students are required to get good learning outcomes. However, some students get low learning outcomes, one of the factors that affects learning outcomes is self-awareness. Low student self-awareness is the cause of low learning outcomes. This research method is quantitative with descriptive and correlational research types. The population in this study was 7,002 KIP recipient students studying at Universitas Negeri Padang who were active in the January-June 2024 semester, with a sample of 382 students selected using the simple random sampling technique. The data was processed using descriptive analysis techniques with a percentage formula and correlational analysis techniques with Pearson product moment. The results of this study indicate that (1) self-awareness is in the high category (65.97%); (2) learning outcomes are in the moderate category (69.9%); and (3) the results of the correlation analysis show a positive and significant relationship between self-awareness (X) and learning outcomes (Y) with a calculated r value of 0.429 with a significance level of <0.005 at a moderate relationship level. A significant positive relationship means that the higher the self-awareness, the higher the student's learning outcomes. Based on the results of this study, counselors can provide assistance to improve self-awareness and student learning outcomes through information services, group counseling services and group guidance services.